An Investigation on the Preference Approach in Experiencing Open and Distance Learning Methods - Masyitah Md Nujid; Duratul Ain Tholibon (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
Open and distance learning (ODL) has become an alternative in teaching and learning (T&L) while the COVID-19 pandemic crisis struck the world globally in December 2019. However, the preferred tool and platform to be chosen in the transition period among students remain uncertain. The purpose of this study was to assess and investigate the effect of T&L preference techniques and technologies chosen by employing ODL in universities during the pandemic. This research adopted a descriptive approach and a quantitative survey was used to collect the necessary data. The questionnaire consisted of 14 questions and was separated into two parts: demographic information and undergraduate students' preference towards online class technology during the COVID-19 pandemic. Four themes and 16 sub-themes were identified in the set of questions in the survey. The results of the analysis revealed that ODL is the preferred method with WhatsApp social media platform as the medium for communication between educators and learners. Educators might consider devoting additional attention to improving teaching and learning practices in open and distance learning in choosing the right approaches and platform to be used through online and offline classes.